Biodegradation and Bioremediation of Polluted Systems - New Advances and Technologies 2015
DOI: 10.5772/60943
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of Using FTIR Spectroscopy for Assessing the Maturity of Sewage Sludge and Olive Oil Waste Co-composts

Abstract: Composts prepared using different solid and liquid organic wastes from various sources can be used as growing media when these materials present adequate proprieties for plant development. The stability and maturity are among the main characteristics of composts. The purpose of this study is to recommend specific bands of the IR spectrum recorded on different composts to enable qualitative and rapid monitoring of the stages of biodegradation during composting. "t the beginning of humification, the significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Absorption bands around 2937 and 2845 cm −1 indicate the C−H stretching of both methyl and methylene groups in lignin. 37 It can be introduced that the majority of lignin side chains were decomposed after sintering of the composite at 500 °C for 2 h. 38,39 The reduction of FT-IR bands of the original lignin compared with TiO 2 /lignin in the range of 1600−1044 cm −1 can reflect the structural changes of lignin during increasing temperature to 500 °C for composite preparation. 40 Many bands, such as C−H deformations (1384 cm −1 ), methoxyl deformation (1420 cm −1 ), and C−O deformation in primary and secondary alcohols (1080 and 1044 cm −1 ), and aromaticbonded oxygen (1266 cm −1 ) groups, were considerably reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption bands around 2937 and 2845 cm −1 indicate the C−H stretching of both methyl and methylene groups in lignin. 37 It can be introduced that the majority of lignin side chains were decomposed after sintering of the composite at 500 °C for 2 h. 38,39 The reduction of FT-IR bands of the original lignin compared with TiO 2 /lignin in the range of 1600−1044 cm −1 can reflect the structural changes of lignin during increasing temperature to 500 °C for composite preparation. 40 Many bands, such as C−H deformations (1384 cm −1 ), methoxyl deformation (1420 cm −1 ), and C−O deformation in primary and secondary alcohols (1080 and 1044 cm −1 ), and aromaticbonded oxygen (1266 cm −1 ) groups, were considerably reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The spectrum of kraft lignin also shows the absorption peak at 3430 cm –1 which is assigned to OH stretching from alcoholic and phenolic hydroxyl groups of lignin structure. Absorption bands around 2937 and 2845 cm –1 indicate the C–H stretching of both methyl and methylene groups in lignin . Bands at 1500–1000 cm –1 can be attributed to the presence of many functional groups, including aliphatic C–H, C–O, C–O–C groups, and C–C bond.…”
Section: Resultsmentioning
confidence: 99%
“…To further quantify the effectiveness of the hydrolysis method using N. mirabilis digestive fluids, FTIR was also used to quantify the changes in the structure and functional group distortion of the agro-waste. One of the major advantages of the FTIR is its ability to analyse samples in any state (liquid or gas) and to characterise the evolution of the substrate structures when samples are extracted from solids [62]. These advantages are also important in providing information about the substrate state (i.e., mixed agro-waste) in the FTIR spectrum [63].…”
Section: Ftir Analysis For Mixed Agro-wastementioning
confidence: 99%
“…The interaction of hydroxyl groups with hydrogen bonds explains the wide profile of this band and the fact that the wave number is lower than that of a free OH hydroxyl [24]. El Fels et al [67] reported that the 3,000-2,800 cm -1 region reflects the hydrophobic properties of aliphatic OM. The peak observed at 2,950 cm -1 is due to methyl derived from methylene C-H aliphatic groups.…”
Section: Ftir Spectroscopic Analysismentioning
confidence: 95%